(untitled) (Journal of Economic Research & Business Administration, 2016)
In any operation decision-making process is almost always associated with uncertainty and risk. Terms of uncertainty, whenmanagerial decisions are made, characterized by inaptitude to estimate the value of the results. Usually, given case occurs due to many complex and unexplored fac-tors, consequently, it is difficult to obtain reliable and accurate informa-tion.In practice, only one variable parameter may be unknown (e.g., sales volume or costs), additionally, the values of several variables can be de-pendent on the other variables. As a result, different values may occur, even values of one case can be connected with the previous values.In such cases forthe leaders of organization for making optimal managerial deci-sions effective analytical tool is a decision tree. The article describes an example of managerial decision-making un-der conditions of uncertainty,using a decision tree based on the indicators LLP “Dauir Service”. In addition, the methods for determining break-even point under risk and uncertainty, and the method of determining the de-gree of reliability of probability of uncertainty are considered, the basic criteriafor decision-making are identified.